FINANCIAL DEVELOPMENT, ECONOMIC FREEDOM AND ECONOMIC GROWTH: NEW EVIDENCE FROM TUNISIA - Zaïbi Oussama; Ahmed Hachicha; Fatma Hachicha (Economic Review)
This article investigates the effect of financial development on economic growth conditions well-developed institutions in Tunisia as a case study during the period 1980-2014, using the generalized moment method (GMM) to analyze the panel data. We have empirically examined the relationship between financial development and institutions using the index of economic freedom as an institutional variable. It has been found that economic freedom can be used as a proxy of developed institutions and that the effect of financial development on economic growth improves in the presence of the variable of economic freedom. We have also found that economic freedom is beneficial to growth and favors the relationship between financial development and the developed institutions and their combined effects on economic growth. These findings suggest the need to promote greater economic freedom and well-developed institutions to improve the relationship between financial development and economic growth.